Motivational Compensation Design for Surgeon in Neurosurgical Group Services in Surabaya - Asra Al Fauzi; Denny Bernardus (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
An effort was made to fulfill one of the citizen's fundamental rights, which was known as the right to acquire health services, and the development of health care was part of that endeavor. In addition, it was an investment made to help promote the growth of the economy and the alleviation of poverty. To improve the general welfare of the community, the Surabaya Neuroscience Institute worked towards implementing various health development initiatives, particularly those linked with neurological conditions. The effectiveness of the Surabaya Neuroscience Institute's staff members was a critical factor in determining its ability to achieve its goals, vision, and mission. In order to reach their full potential, the physicians who worked at the Surabaya Neuroscience Institute needed to maintain a high level of motivation. An effective remuneration scheme will support the motivation of the worker. On the other hand, when it came to the implementation of this compensation scheme, the culture that prevailed in the medical area was quite distinct. In addition to the justice components, the ethical and seniority aspects continued to be very relevant for both the performance of physicians and the remuneration model. The version of physicians at the Surabaya Neuroscience Institute needed to be improved. Thus, this study aimed to develop a motivating compensation system that might do so. In this study, a descriptive qualitative method alongside an in-depth interview was used, and the respondent was chosen using a method known as non-random purposive sampling. A total of six individuals were utilized to represent the population of 19 members at the Surabaya Neuroscience Institute. In light of the findings, an examination of the respondents' points of view revealed that almost all of them believed there was still an issue with the level of motivation exhibited by the physicians working at the SNeI. Concerning the compensation system, the results showed that the design of the financial compensation is deemed suitable. Still, the issue of nonfinancial compensation needs to be studied and improved because it can significantly impact the performance of physicians.